Weed population and biomass in direct seeded rice (Oryza as influenced by irrigation sativa) - R. BALASUBRAMANIAN; J. KRISHNARAJAN (Indian Journal of Agronomy, 2001)
, The response of lowland weeds and rice (Oryza sativa L.) to various water management practices was determined at the wetland farms of Coimbatore, during the rainy and winter seasons (1 997 98 and 1998 99). Weed population and growth were generally higher during the rainy season than winter season. Variation in irrigation regimes brought about distinct changes in weed growth and establishment in rice fields. Irrigating 5 cm depth 1 day after disappearance of ponded water in transplanted rice recorded the lowest number of weeds, viz. grasses, sedges and broad leaved weeds and the lowest dry weight of weeds. However, irrigating 5 cm depth 1 day after disappearance of ponded water in direct seeded rice and continuous submergence of 2.5 cm depth were at par with transplanted rice. Lower water regimes recorded the maximum weed population and biomass due to lack of flooding. Transplanted rice recorded more water use than the direct seeded rice. The highest grain yield was recorded with direct seeded rice during the rainy and by transplanted, rice during winter season. Benefit :cost ratio was more for the higher water regimes of direct seeded rice than transplanted rice as transplanted rice required more labour for raining nursery and for transplanting.